Menganalisis Pembelajaran Kreatif yang Diterapkan di Kelas Rendah SDS Parulian 2 Medan - Marsya Grace Lady Waruwu; Naomi Meiati Sinaga; Aisyah Putri; Agnes Yohana Lumban Batu; Asri Natalia Sitompul; Marini Anita Simangunsong; Jelika Taruli Gultom; Sindi Miranda Br Manullang (Journal of Student Research, 2025)
This study aims to analyze the implementation of creative learning among lower-grade students at SDS Parulian 2 Medan. The research employed a descriptive qualitative method with data collected through observation and questionnaires. The subjects were 51 students from grades II and III. The observation results indicate that teachers still tend to use conventional methods; however, students appeared more enthusiastic when the lessons were accompanied by creative activities such as educational games, quizzes, and the use of concrete media. The questionnaire findings support this, showing that 66.1% of students expressed liking creative learning, 17.6% stated it was average, and 16.3% reported less interest. The combined average score of 2.49 indicates that students’ interest in creative learning is at a moderate to high level. These findings highlight that the application of simple creative strategies can provide more enjoyable and meaningful learning experiences for elementary students. The study recommends that teachers optimize the use of media and varied methods to make learning more engaging and aligned with students’ developmental needs.